(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
Among the functions of the concept of legal good are those of verifying the constitutionality of criminal types and their respective teleological interpretation. In the field of economic criminal law, where diffuse legal assets are protected, the concept of the legal good is especially reinforced as a mechanism to inhibit the merely formal application of criminal types. We start from this premise in order to analyse the normative elements of the criminal offence of keeping undeclared deposits abroad, in particular the “competent federal office”, the minimum value of the deposits and the base date to be considered for the characterization of the crime.